Wybrane aspekty pracy zawodowej instruktorów fitness = Chosen aspects of professional work of fitness instructors - Paweł Fryderyk Nowak; Marta Chalimoniuk-Nowak (Kazimierz Wielki University, 2016)
Nowak Paweł F., Chalimoniuk-Nowak Marta. Wybrane aspekty pracy zawodowej instruktorów fitness = Chosen aspects of professional work of fitness instructors. Journal of Education, Health and Sport. 2016;6(5):298-315. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.53087 http://ojs.ukw.edu.pl/index.php/johs/article/view/3527   The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 25.05.2016.   Wybrane aspekty pracy zawodowej instruktorów fitness  Chosen aspects of professional work of fitness instructors  Paweł F. Nowak1, Marta Chalimoniuk-Nowak2   1Wydział Wychowania Fizycznego i Fizjoterapii, Politechnika Opolska 2Polskie Stowarzyszenie Trenerów Zdrowia     Słowa kluczowe: instruktorzy fitness, kompetencje, fitness, promocja zdrowia. Key words: fitness instructor, competencies, fitness sector, health promotion.   Streszczenie Cel Celem niniejszej pracy była charakterystyka wybranych aspektów pracy zawodowej trenerów, instruktorów pracujących w klubach fitness, na podstawie ich opinii, jak i opinii pracodawców branży fitness i wellness. W pracy wyszczególniono charakterystykę zatrudnienia, świadomość celu wykonywanej pracy, pożądane kompetencje oraz satysfakcję z pracy. Materiał i metody W badaniach wzięło udział 144 instruktorów pracujących w klubach fitness, a także 36 pracodawców - właścicieli klubów. Posłużono się metodą sondażu diagnostycznego. Wykorzystanym narzędziem badawczym był autorski kwestionariusz ankiety. Wyniki Pracę trenera, instruktora fitness wykonują osoby młode - (82% z nich nie przekroczyło 35 roku życia). W zawodzie zaobserwować można dużą rotację, o czym świadczy krótki staż pracy instruktorów; aż 77,8% badanych to pracujący w tej branży poniżej 2 lat. Ponad 90% pracujacych w charakterze instruktora fitness ma wykształcenie wyższe (licencjackie bądź magisterskie). Zaledwie 8,33% instruktorów jest zatrudnionych na podstawie umowy o pracę. Według pracodawców branży fitness najważniejszym celem pracy instruktora jest tworzenie długotrwałych relacji z klientami. Tak rozumiany cel pracy jest bliski przede wszystkim młodym pracownikom o krótkim stażu. Pracodawcy przedkładają tzw. twarde kompetencje nad cechy osobowości u pracowników branży fitness. Natomiast najważniejszymi predyspozycjami do zawodu w ocenie instruktorów są charyzma i komunikatywność. Wnioski Pozycja zawodowa trenera instruktora, fitness jest wysoce niestabilna, to rodzaj pracy raczej dodatkowej. Ta sytuacja nie skłania do rozwoju i identyfikacji pracowników z miejscem pracy.   Abstract   Aim The characteristics of selected aspects of fitness instructors' work and trainers - based on their opinion and their employers in wellness&fitness sector was the main objective of this article. The characteristics of employment, awareness to work, competencies valued in this work and job satisfaction was specified in this thesis. Material and methods Fitness instructors (144) and 36 employers - managers or owners of fitness clubs - were researched using author's survey questionnaire as a research tool. Results Majority young people perform a job coach, fitness instructor (85% of them are below 35). In this profession a high employee turnover is observed, evidenced by the short length of service of instructors - 77.8% of the respondents are working in this sector less than 2 years. More than 90% of examined fitness instructors hold a university degree (bachelor or master). Only 8,33% of instructors are employed under a contract of employment. According to the fitness sector employers the most important goal of instructor's work is creating long-term relationships with clients. With the aim of the work, thus understood, identifying the most youngest workers, with short work experience. Employers submit hard competencies over the personality traits of employees in fitness sector. The most important predispositions to the profession, in the opinion of the instructors, are charisma and good communication skills. Conclusions Professional position of fitness trainers and instructors is highly instable, it is rather a kind of surplus job. This situation does not encourage professional development or identification of employees with the workplace.